20. Falciform ligament herniation treated with combined trans-peritoneal laparoscopic dissection and abdominal wall repair by hand-interrupted suture: A case series report and review of literature - Son, Tran Que; Hung, Tran Manh; Hoc, Tran Hieu; Truong, Trieu Van; Kien, Nguyen Trung; Thanh, Nguyen Tuan; Minh, Do Duc; Thanh, Nguyen Tien; Anh, Ha Duc; Nha, Vu Thi; Phuong, Nguyen Thi Mai; Tuyen, Phung Van; et al. (Tạp chí Nghiên cứu Y học, 2023)
Falciform ligament hernia is a very rare internal hernia and is difficult to diagnose before surgery. Most reported cases are incisional hernias secondary to prior abdominal surgery. We report three cases of primary falciform ligament herniation into the epigastric region that was repaired by the intra-peritoneal laparoscopic approach combined with an extra-abdominal small skin incision. All laparoscopic procedures were performed without conversion to laparotomy, and all specimens were histopathologically diagnosed as lipomas. Three patients successfully recovered and were discharged on surgical days 2, 2, and 5, respectively. There were no complicationor recurrence during the 12-month follow-up. This technique is safe and feasible for repairing midline abdominal wall herniation. If the hernia orifice is less than 2cm in diameter, the abdominal wall defect may be improved by this procedure using Safil 1.0 or Vicryl 1.0 suture without mesh.